2011
DOI: 10.1785/0120090380
|View full text |Cite
|
Sign up to set email alerts
|

Moment-Tensor Determination by Nonlinear Inversion of Amplitudes

Abstract: International audienceWe propose an inversion method of the direct wave amplitudes P, SV, and SH to determine the general moment tensor (MT) and estimate the associated uncertainties. This method is a generalization of the one we developed to determine the double-couple (DC) or fault-plane solution from sparse observations in reservoir contexts (Godano et al., 2009). Like the previous one, it is based on a simulated annealing inversion algorithm. First, we test the reliability of this new method on synthetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…On the other hand, Horalek et al (2010) studied 45 of the largest M 1.4-2.9 earthquakes from a 2003 borehole injection experiment and found that DC mechanisms dominated the sequence. Godano et al (2011) studied four microearthquakes induced in the Soultz-sous-Forets HDR reservoir and obtained moment tensor solutions having high uncertainty associated with low isotropic and CLVD components. Deichmann and Giardini (2009) found that seismicity induced by the enhanced geothermal system of Basel, Switzerland, generally have focal mechanisms that indicate shear failure on preexisting faults, with some focal mechanisms showing signs of non-DC components with volume change.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Horalek et al (2010) studied 45 of the largest M 1.4-2.9 earthquakes from a 2003 borehole injection experiment and found that DC mechanisms dominated the sequence. Godano et al (2011) studied four microearthquakes induced in the Soultz-sous-Forets HDR reservoir and obtained moment tensor solutions having high uncertainty associated with low isotropic and CLVD components. Deichmann and Giardini (2009) found that seismicity induced by the enhanced geothermal system of Basel, Switzerland, generally have focal mechanisms that indicate shear failure on preexisting faults, with some focal mechanisms showing signs of non-DC components with volume change.…”
Section: Introductionmentioning
confidence: 99%
“…The basic tool for quantifying earthquake sources is the seismic moment tensor. The moment tensor is calculated using amplitudes of seismic waves (Vavryčuk et al 2008; Fojtíková et al 2010; Godano et al 2011), amplitude ratios (Miller et al 1998; Hardebeck & Shearer 2003; Jechumtálová & Šílený 2005) or full waveforms (Dziewonski et al 1981; Sipkin 1986; Kikuchi & Kanamori 1991; Šílený et al 1992). The inversion of full waveforms is a widely used approach applicable on all scales: from micro‐ to large macro‐earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Here we assume the focal mechanism of the small induced events can be represented by pure double couples (Rutledge & Phillips, 2002), though it is possible that a volume change or Compensated Linear Vector Dipoles (CLVD) part may also exist, especially in hydraulic fracturing cases, and the nondouble-couple components are informative for understanding the rock failure under highpressure fluid (Ross & Foulger, 1996;Jechumtálová & Eisner, 2008;Šílený et al, 2009;Song & Toksoz, 2010). The constraining of focal mechanism as double couple (DC) can eliminate the spurious non-DC components in the inversion raised by modeling the wave propagation in anisotropic medium with isotropic Green's functions or inaccuracy of the velocity model (Šílený & Vavryčuk, 2002;Godano et al, 2011). However, if strong non-DC components actually exist in the source rupture process, the determined fault plane may be biased (e.g., Jechumtálová & Šílený, 2001;Jechumtálová & Šílený, 2005).…”
Section: Focal Mechanism Determination Methodsmentioning
confidence: 99%
“…There have been many studies on determining the focal mechanism of the induced seismicity in cases of enhanced geothermal system development, mining and hydraulic fracturing. Godano et al (2011) used the direct amplitudes of P, SV and SH to study the focal mechanisms of induced microearthquakes in a geothermal site using full-space homogeneous velocity models. Nolen-Hoeksema et al (2001) used the first half cycle after the first arrivals from the observed seismograms and synthetics from full-space Green's functions to determine the focal mechanisms of several hydraulic fracture events.…”
Section: Introductionmentioning
confidence: 99%